Establishment and application of DNA barcode identification method for species of shark fins - JIANG Xiaoxia; SHA Caihua; LUO Baozheng; SHAO Jianhong; XU Bowen; HUANG Haichao; ZHAO Fuzhen; ZHOU Aobaixue; CHEN Xuan (浙江大学学报. 农业与生命科学版, 2024)
Accurate identification of the species of shark fins has been a significant challenge for customs and other law enforcement agencies to fulfill Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). In this study, we established a DNA barcode identification method for cytochrome c oxidase subunitⅠ (COⅠ) gene of shark species, applied it to 113 shark fin samples intercepted at Zhuhai-Macao Port, and identified a total of 19 species, dominated by Carcharhinidae family species such as Prionace glauca and Carcharhinus falciformis. 56.64% of the samples were listed in the 2019 version of the CITES Appendix Ⅱ, and 90.27% were listed in the 2023 version of the CITES Appendix Ⅱ. The analysis results showed that the established method produced specific amplifications and obtained valid sequences for all samples. The intra-specific genetic distance of the measured species was ≤2.08% (average of 0.63%), and the inter-specific genetic distance ranged from 2.42% to 27.27% (average of 15.37%). The smallest inter-specific genetic distance was greater than the largest intra-specific genetic distance. The average inter-specific genetic distance was 23 times greater than intra-specific genetic distance. All species clustered in the phylogenetic tree based on their degree of kinship. Species from the same family further clustered in sub-branches. There was no cross-distribution of species among sub-branches. In summary, the DNA barcode technique based on theCOⅠ gene could accurately identify the species of shark fins, which is important for the diversity conservation of sharks.